2008
DOI: 10.1037/0033-295x.115.3.760
|View full text |Cite
|
Sign up to set email alerts
|

Mental models and the suppositional account of conditionals.

Abstract: The mental model theory of conditional reasoning presented by P. N. Johnson-Laird and R. M. J. Byrne (2002) has recently been the subject of criticisms (e.g., J. St. B. T. Evans, D. E. Over, & S. J. Handley, 2005). The authors argue that the theoretical conflict can be resolved by differentiating 2 kinds of reasoning, reasoning about possibilities given the truth of assertions and reasoning about the truth of assertions given possibilities. The standard mental model theory accounts for the former kind of reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(140 citation statements)
references
References 40 publications
11
123
3
3
Order By: Relevance
“…Finally, older adolescents and adults who construct a three-model representation by adding two models (i.e., : p : q, and : p q) should deem the conditional true for p & q cases, false for p & not-q cases, not-p cases being judged as irrelevant, a response pattern corresponding to the well-known defective 1 or De Finetti truth-table of the conditional. These predictions have been verified in several studies (Barrouillet et al, 2008;Gauffroy & Barrouillet, 2009. In the same way, our theory makes straightforward predictions concerning the probability task.…”
Section: The Suppositional Conditional and Its Putative Developmentsupporting
confidence: 61%
See 2 more Smart Citations
“…Finally, older adolescents and adults who construct a three-model representation by adding two models (i.e., : p : q, and : p q) should deem the conditional true for p & q cases, false for p & not-q cases, not-p cases being judged as irrelevant, a response pattern corresponding to the well-known defective 1 or De Finetti truth-table of the conditional. These predictions have been verified in several studies (Barrouillet et al, 2008;Gauffroy & Barrouillet, 2009. In the same way, our theory makes straightforward predictions concerning the probability task.…”
Section: The Suppositional Conditional and Its Putative Developmentsupporting
confidence: 61%
“…Importantly, our theory departs from the traditional mental model approach by assuming different epistemological statuses for the different types of models constructed (Barrouillet et al, 2008). Whereas the conditional is deemed true for those cases that match the initial model that comes spontaneously to mind, the alternative models constructed through fleshing out have a different status.…”
Section: The Suppositional Conditional and Its Putative Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…3) that with increasing developmental level of inductive and deductive reasoning, reaction times to speed and control of processing tasks decreased and working memory capacity increased. In line with these findings, Barouillet and colleagues (Barrouillet et al 2000(Barrouillet et al , 2008Markovits and Barrouillet 2002) showed that the development of deductive reasoning is a process of constructing mental models for real problems based on the content and knowledge available. The complexity of the models depends on working memory because more capacity allows for more models and more pointers from them to information in long-term memory.…”
Section: Dynamic Developmental Relationsmentioning
confidence: 67%
“…The model theory postulates that the meaning of clauses and knowledge can modulate the interpretation of connectives so that that they diverge from logical interpretations (57). Evidence bears out the occurrence of such modulations (58), and independent experimental results corroborate the model theory of conditionals (59)(60)(61)(62). Critics, however, have yet to be convinced (63, but cf.…”
Section: Effects Of Contentmentioning
confidence: 71%